Political, Religious and Social Unrest in Yemen in the 18th And 19th Centuries during the Late Ottoman Dynasty - Atabik, Ahmad; Mustaqim, Muhamad (Journal of Islamic Thought and Civilization, 2020)
Yemen is a country with a long history of world civilization, both before and after the emergence of Islam. For the pre-Islamic period, the Qur’ān has talked about various tribes living in Yemen, such as the 'Ad and the Saba’ people. In the Islamic period, many Yemeni people played an important role in spreading Islam to various parts of the world. This article discusses the situation of Yemen in the 18th and 19th centuries, when massive turmoil occurred in the society. In terms of politics, Yemen was surrounded by a growing number of dynasties, such as the Ottoman dynasty of Turkey which belonged to the Sunni sect, the Safavid dynasty of Iran which belonged to the Shi’a sect, and the emergence of the Wahhabi movement in the Hejaz. At that time, Islamic states were being colonized by western countries, such as Egypt which was controlled by the French. Such conditions led to political turmoil in Yemen. In religious sense, there were various sects claiming truth one another in Yemen, among them were the Zaydi Shia and the Ismaili Shia. This caused hostilities among Muslim people at that time in Yemen. Keeping in view the social aspect, there was a social gap which led to feuding among the various social components in Yemen. The people of Sana’a city and its administration frequently went through unstable situations; moreover, wars among tribes for material purposes also occurred.